Management of forgotten double J stent and its complications: a single center experience - Manharlal, Tilala Yash; Panda, Sabyasachi; Swain, Samir; Tripathi, Abhilekh; Sharma, Sachin; Anshuman, Jateen; Behera, Kishore Kumar (International Surgery Journal, 2023)
Background: The objective of this study is to elaborate presenting symptoms related to forgotten ureteric double J stent, various complications related to it, it’s management and possible preventive measures by which morbidity related to forgotten double j stent can be avoided Methods: Total 30 patients admitted in our institution from January 2018 to December 2022 with double j stent in situ with more than 6 months without any indication of prolonged stenting have been included. Retrospectively analysed the collected data from the institutional records. Results: Mean age was 42.9±12.4 yrs (18-70 yrs), mean indwelling time was 41±12.4 months (9 months to 11 yrs), Post ureterorenoscopic lithotripsy stenting was most common indication in 10 (33.3%) and most common presenting symptom was flank pain with storage lower urinary tract symptoms in 18 (60%) patients. The 22 (73.3%) patients had moderate to severe encrustation, 6 (20%) patients had fragmentation of stent and 1 (3.33%) patient had ipsilateral non-functioning kidney as one of the most feared complications. Per-cutaneous nephrolithotomy was single most employed modality of management in 15 (50%) patients, while 8 (26.67%) patients required multimodality treatment. The indwelling time and degree of encrustation showed positive strong correlation with parson correlation coefficient 0.973 which was statistically significant (p=0.014). Conclusions: With prolonged indwelling double J stents may produces some serious complications which may require multimodality approach to treat. Such conditions can be reduced via proper patient’s education and counselling.